2017
DOI: 10.4992/jjpsy.88.16308
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between motivational regulation strategies, motivational factors, and learning behaviors outside the classroom

Abstract: Relationships between motivational regulation strategies, motivational factors, and learning behaviors outside the classroom Takatoyo Umemoto (Kyushu Women's University) and Kenshiro Tanaka (University of Yamanashi)This study examined the relationships among motivational regulation strategies, motivational factors, and learning behaviors outside the classroom. There are three subtypes of motivational regulation strategies: autonomous regulation strategies, cooperative strategies, and performance-focused strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…"Intrinsic value" refers to the belief about importance, utility, and interest of a task (Pintrich & De Groot, 1990). The results of Umemoto and Tanaka (2017) showed that intrinsic value was positively associated with autonomy-regulation strategies. In contrast, intrinsic value was not associated with performance-regulation strategies.…”
Section: Self-regulation Of Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…"Intrinsic value" refers to the belief about importance, utility, and interest of a task (Pintrich & De Groot, 1990). The results of Umemoto and Tanaka (2017) showed that intrinsic value was positively associated with autonomy-regulation strategies. In contrast, intrinsic value was not associated with performance-regulation strategies.…”
Section: Self-regulation Of Motivationmentioning
confidence: 99%
“…Although motivational research has a long history, recent research has begun to examine how to regulate the motivation itself. Especially, self‐regulated learning (SRL) research has been elucidating how students can learn by themselves (Zimmerman & Schunk, 2011), and researchers have conceptualized this psychological mechanism with the term “motivational regulation” (Ito & Shinto, 2003; Umemoto & Tanaka, 2017; Wolters & Benzon, 2013). Motivational regulation means an aspect of the self‐regulation function that promotes and maintains the motivation to learn effectively and efficiently (Umemoto, 2015; Wolters, 2003).…”
Section: Self‐regulation Of Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured students' learning behaviors, based on the Behavioral Engagement Scale [8] (four items, α=.81), the metacognitive strategy scale [9] (six items, α=.72), and the Academic Help-Seeking Scale [10] (six items). Moreover, the Academic Help-Seeking Scale was comprised of two subscales: adaptive help-seeking (three items, α=.73) and dependent help-seeking (three items, α=.84).…”
Section: Learning Behaviorsmentioning
confidence: 99%
“…Although motivational factors and engagement learning strategies have been researched in diverse learning contexts (Ryan & Deci, 2000;Bong, 2001;Seki, 2014;Umemoto & Tanaka, 2017), two areas need more attention. First, previous studies on motivational factors have focused on school, subject level, gender and attitude variables toward learning in general (Ramseier, 2001;Gedera, Williams & Wright, 2015;King, 2016).…”
Section: Introductionmentioning
confidence: 99%